The importance of illumination in nest site choice and nest characteristics of cavity nesting birds - Paweł Podkowa (Nature Portfolio, 2017)
Abstract Light has a significant impact on many aspects of avian biology, physiology and behaviour. An increasing number of studies show that illumination may positively influences birds’ offspring fitness by e.g. acceleration of embryo development, stimulation of skeleton growth or regulation of circadian rhythm. Because nest cavities have especially low illumination, suitable light levels may be especially important for species which nest there. We may therefore expect that birds breeding in relatively dim conditions should prefer brighter nest sites and/or evolve behavioral mechanisms to secure sufficient light levels in the nest. Using nest boxes with modified internal illumination, we experimentally tested whether light regime is a cue for nest site selection of secondary cavity-nesting species. Additionally, we investigated whether nest building strategies are tuned to internal illumination. Our results demonstrate that, nest boxes with elevated illumination were chosen twice as often as dark nest boxes. Moreover, birds built higher nests in dark nest boxes than birds in boxes with elevated illumination, which suggests a mechanism of compensating for low light conditions. Our results provide the first experimental support for the idea that nest site choice and nest building behaviour in cavity-nesting birds are influenced by ambient illumination.